2016
DOI: 10.1007/s13197-016-2188-x
|View full text |Cite
|
Sign up to set email alerts
|

Malting process optimization for protein digestibility enhancement in finger millet grain

Abstract: Finger millet (Eleusine coracana) is a nutritious, gluten-free, and drought resistant cereal containing high amounts of protein, carbohydrate, and minerals. However, bio-availability of these nutrients is restricted due to the presence of an excessive level of anti-nutrient components, mainly phytic acid, tannin, and oxalate. It has been shown that a well-designed malting/germination process can significantly reduce these anti-nutrients and consequently enhance the nutrient availability. In the present study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 30 publications
7
24
1
Order By: Relevance
“…After germination, a significant increase in protein content (P<0.00) was observed in both species. These results agree with previous findings in germinated amaranth flour (Chauhan et al, 2015;Hejazi & Orsat, 2016), although other authors reported no significant change in protein due to germination (Colmenares & Bressani, 1990;Kanensi, Ochola, Gikonyo & Makokha, 2011). Gamel et al (2005) reported a significant reduction of amaranth protein content during germination, attributed to proteolytic enzyme activity.…”
Section: Chemical Compositionsupporting
confidence: 92%
See 1 more Smart Citation
“…After germination, a significant increase in protein content (P<0.00) was observed in both species. These results agree with previous findings in germinated amaranth flour (Chauhan et al, 2015;Hejazi & Orsat, 2016), although other authors reported no significant change in protein due to germination (Colmenares & Bressani, 1990;Kanensi, Ochola, Gikonyo & Makokha, 2011). Gamel et al (2005) reported a significant reduction of amaranth protein content during germination, attributed to proteolytic enzyme activity.…”
Section: Chemical Compositionsupporting
confidence: 92%
“…But also, bioactive compounds such as GABA, -oryzanol and phenolic content can be improved with seeds germination, as has been reported in rice (Cáceres, Martínez-Villaluenga, Amigo & Frias, 2014). Particularly, in the case of amaranth, germination increases the amount of phenolic compounds, flavonoid content, protein digestibility and antioxidant activity, as well as decreases anti-nutritional compounds (Perales-Sánchez et al, 2014;Hejazi & Orsat, 2016, Colmenares & Bressani, 1990. Besides the improvement in nutritional properties, germination affects the physiochemical properties of the resulting flour (Gamel et al, 2006;Siwatch, Yadav & Yadav, 2017;Chauhan, Saxena & Singh, 2015).…”
Section: Introductionmentioning
confidence: 80%
“…Reduction in tannin after malting has widely been reported in literature [23]. Hejazi and Orst [25], working with finger millet malted at different durations (24 h, 48 h and 72 h) were able to show a positive reduction between tannin content and germination duration. The reduction is mainly attributed to steeping step of the finger millet grains.…”
Section: Effect Of Compositing Malted Finger Millet Flour With Precoomentioning
confidence: 81%
“…Astringency is because of high levels of bitter condensed tannins and polyphenols found in unmalted millet flour [28]. When finger millet is malted level of tannins and polyphenols are reduced by action of inherent hydrolytic enzymes such as polyphenol oxidase to lower molecular weight compounds that are less bitter [25]. Additionally, compositing malted millet flour with precooked cowpea flour (has low amount of polyphenols), further reduces astringency of the complementary finger millet porridge.…”
Section: Pca Characteristics Of Sensory Attributes Of Complementary Pmentioning
confidence: 99%
“…The significant increase in protein content observed in flour from germinated millet grains is attributed to an increased water activity that activates hydrolytic enzymes (Nonogaki, Bassel, & Bewley, 2010) as well as compositional changes associated with dry matter loss following the degradation of other constituents (Abdelhaleem, El Tinay, Mustafa, & Babiker, 2008). The physical mechanisms and biochemical reactions that explain the observed increase in bioavailability of protein content during the germination process are strongly associated with the morphology of the finger millet seed (Hejazi & Orsat, 2016). In the finger millet, endosperm Phytates form complexes with proteins, hence causing a detrimental impact by reducing protein digestibility and amino acid availability (Selle, Cowieson, Cowieson, & Ravindran, 2012).…”
Section: Optimal Processing Conditions Of Millet Flourmentioning
confidence: 99%